A Review on Complications and Management of Aluminium Phosphide (Rice Pill) and Zinc Phosphide Poisoning - Saravani, Khadijeh; Alizadeh Ghamsari, Anahita; Dadpour, Bita; Ghassemi Toussi, Alireza; Mousavi, Seyed Reza; Pouramiri, Farah (Novelty in Biomedicine, 2024)
Background: Various fumigant products containing aluminium phosphide, known as rice pills, are widely used to kill insects in many parts of Iran, including the northern provinces. Poisoning with zinc phosphide as a rat poison also has the same side effects as aluminium phosphide. This poisoning has no specific antidote, and the treatment is auxiliary, and one of the effective auxiliary treatments is L-carnitine. This review study aimed to determine the prevalence of aluminium phosphide poisoning and treatment with intravenous L-carnitine. Materials and Methods: This study was a narrative review conducted in 2023. Search keywords aluminium phosphide, zinc phosphide, intravenous L-carnitine, and poisoning in Persian and English languages in databases including Magiran, PubMed, Wiley, Science Direct, web of Sciences, SID, Scopus, and Google Scholar were done from 1970 to 2022. Relevant articles were identified, and the most important and valuable points were presented after review. Results: According to the findings of most studies, aluminium phosphide pills had the most adverse effects as toxic substances. Conclusion: Due to the prevalence of its consumption among young people with low education levels, there was a need for physicians to treat these patients as quickly as possible accurately. It is also necessary to raise awareness about its potentially dangerous side effects and to monitor closely the distribution of this poisonous pill in its distribution centers. Moreover, the quick start of supportive treatment with antioxidants and L-carnitine can help in this poisoning that does not have a specific antidote. Very effective and useful.